2018
DOI: 10.1021/acsami.8b07918
|View full text |Cite
|
Sign up to set email alerts
|

Defect-Induced Exchange Bias in a Single SrRuO3 Layer

Abstract: Exchange bias stems from the interaction between different magnetic phases, and therefore, it generally occurs in magnetic multilayers. Here, we present a large exchange bias in a single SrRuO layer induced by helium ion irradiation. When the fluence increases, the induced defects not only suppress the magnetization and the Curie temperature but also drive a metal-insulator transition at a low temperature. In particular, a large exchange bias field up to ∼0.36 T can be created by the irradiation. This large ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…We attribute the origin of THE to defect engineering by ion irradiation, which breaks the bulk inversion symmetry through altering oxygen octahedral rotation and thus produces DMI in thick SRO films. [ 16–19 ]…”
Section: Figurementioning
confidence: 99%
“…We attribute the origin of THE to defect engineering by ion irradiation, which breaks the bulk inversion symmetry through altering oxygen octahedral rotation and thus produces DMI in thick SRO films. [ 16–19 ]…”
Section: Figurementioning
confidence: 99%
“…Here, we use helium (He) ion irradiation to induce "strain doping" in SVO films. Strain doping by irradiation of noble He atoms results in an uniaxial lattice expansion along the out-of-plane direction without changing the in-plane lattice constants [23][24][25]. For instance, Gao et al reported that the out-of-plane lattice parameter in epitaxial La 0.7 Sr 0.3 MnO 3 thin films is continuously and independently manipulated by using He ion irradiation [23].…”
Section: Introductionmentioning
confidence: 99%
“…Polarization dependent X-ray absorption measurements, duly combined with configuration interaction simulations suggest charge transfer from Ni/Mn 3d to Ti 3d orbitals through O 2p orbitals across the SNMO/BTO (SB) interfaces, which can induce magnetism in the BTO spacer layer. The observed exchange bias in SBS heterostructures is discussed considering the pinning of moments due to exchange coupling at SB (or BTO/SNMO) sandwich interface.The exchange bias (EB) phenomenon, described as the shift of isothermal magnetic hyteresis loop in the magnetic field scale, is attributed to unidirectional anisotropy effect [1,2].Ideally an antiferromagnetic (AFM) system possess equivalent energies for the two oppositely aligned magnetic sublattices. Now, the EB effect can be understood considering the exchange coupling of any one AFM sublattice spins with adjacent ferromagnetic (FM) spin arrangements, when the FM/AFM interface system (FM T C > AFM T N…”
mentioning
confidence: 99%
“…The exchange bias (EB) phenomenon, described as the shift of isothermal magnetic hyteresis loop in the magnetic field scale, is attributed to unidirectional anisotropy effect [1,2].…”
mentioning
confidence: 99%